Donizetti's Lucia di Lammermoor - Cammarano, Salvatore, 1801-1852.; Fisher, Burton D.; Cammarano, Salvatore, 1801-1852.; Cammarano, Salvatore, 1801-1852.; Donizetti, Gaetano, 1797-1848.; Scott, Walter, 1771-1832. (Miami : Opera Journeys, 2005)
A comprehensive guide to Donizetti's LUCIA DI LAMMERMOOR, featuring insightful and in depth Commentary and Analysis, a complete, newly translated Libretto with Italian/English side-by side, and over 25 music highlight examples.
Lucia di Lammermoor/Opera Classics Library Series; Title Page; Contents; a prelude ... ; Provenance; Libretto; Discography; Videography; Dictionary of Opera and Musical Terms
Libretto by Salvatore Cammarano after Sir Walter Scott's novel The Bride of Lammermoor (1819).
Text in English; libretto in English and Italian.
Includes discography and videography.
eBooks on EBSCOhost
Keywords: Donizetti, Gaetano, -- 1797-1848.; Lucia di Lammermoor (Donizetti, Gaetano); Operas -- Librettos; Opéras -- Livrets; MUSIC -- Genres & Styles -- Opera; Operas -- Librettos